Primary Squamous Cell Carcinoma Thyroid with Regional Recurrence - Nugroho Akhbar; Benny Issakh (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Background. Primary squamous cell carcinoma (PSCC) of the thyroid is a very aggressive malignancy with a poor prognosis. There is no consensus for the management of primary squamous cell carcinoma (PSCC) of the thyroid, and this is based on rare cases in which the frequency of occurrence is less than 1% of thyroid malignancies. How squamous cell carcinoma originates in the thyroid gland is an interesting topic to discuss, because the thyroid gland does not have a squamous cell epithelium. Case Presentation. A 43-year-old man was admitted to the DR Kariadi Hospital with complaints of a lump on the right neck. In June 2020, the patient complained of a lump in the right neck area with a diameter of about 1x1x1 cm, no pain. Ultrasound of the colli at the regional hospital showed the impression of multiple lymphadenopathy of the right colli level 2-5, and there were cystic nodules with solid parts in the right and left lobes of the thyroid suspected of being benign. An adenectomy operation was performed at a regional hospital and the impression of metastatic squamous undifferentiated carcinoma was obtained. Conclusion. The management of thyroid PSCC is a multimodality therapy, namely surgery, chemotherapy and radiation.